Learning employee-driven innovating: Towards sustained practice through multi-method evaluation. Issue 5 (8th July 2014) - Hasu, Mervi; Honkaniemi, Laura; Saari, Eveliina; Mattelmäki, Tuuli; Koponen, Leena
Abstract : Purpose: – The purpose of this paper is to introduce a workshop process to enhance the learning of employee-driven innovating (LEDI) and to evaluate in multiple ways the practical effects of the LEDI process, which aimed to enhance the employee-driven innovation practices at workplace level in a public organisation. Although front-line employees are increasingly encouraged to participate in innovation, organisations lack multi-level knowledge on the practices, outcomes and effects of participation. Design/methodology/approach: – A six-month development process (LEDI) was conducted to empower front-line hospital support service workers to learn to innovate and to apply this in the services they provide. The process consisted of different themes: future visions, current services, creating new services and evaluations of ideas and innovation embryos. The multi-method evaluation of the process included pre-evaluation of the generated innovation ideas, a developmental evaluation of the selected innovation embryos, a follow-up evaluation of the innovation ideas and an evaluation of the organisational level effect via a quantitative survey. Findings: – The intervention process had positive effects on employee participation and learning to innovate. The conclusion of the four evaluations is that the LEDI process developed a new kind of agency among employees and enabled significant improvements to services. The evaluation of the organisation-level effect revealed that the process had also improved the views regarding preconditions for development. Originality/value: – The intervention method is a practical application of employee-driven innovation conception that is validated as practical and effective at workplace level. The process is a viable method for enhancing workers' innovation-related learning in service organisations. The novelty of the method is based on the multi-disciplinary combination of approaches that consist of theories of practice-based innovation, expansive learning and emphatic human-centred service design.